2020
DOI: 10.3906/elk-2001-38
|View full text |Cite
|
Sign up to set email alerts
|

A detailed survey of Turkish automatic speech recognition

Abstract: Significant improvements have been made in automatic speech recognition (ASR) systems in terms of both the general technology and the software used. Despite these advancements, however, there is still an important difference between the recognition performance of humans and machines. This work focuses on the studies conducted in the field of Turkish speech recognition, the progress made in such studies in recent years, the language-specific constraints, the performance results achieved in the applications deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It has been observed that these studies commonly incorporate layers such as GRU, LSTM, and Transformer, resulting in the most successful outcomes among the methods utilized ( Chiu et al, 2018 ; Liu et al, 2018 ; Hsu et al, 2021 ; Yu et al, 2022 ). It has been noted that a majority of ASR studies in existing literature primarily concentrate on languages such as English, Chinese, Spanish, German, and French, whereas there is a scarcity of research focusing on languages within the agglutinative language group, such as Turkish ( Arslan & Barışcı, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that these studies commonly incorporate layers such as GRU, LSTM, and Transformer, resulting in the most successful outcomes among the methods utilized ( Chiu et al, 2018 ; Liu et al, 2018 ; Hsu et al, 2021 ; Yu et al, 2022 ). It has been noted that a majority of ASR studies in existing literature primarily concentrate on languages such as English, Chinese, Spanish, German, and French, whereas there is a scarcity of research focusing on languages within the agglutinative language group, such as Turkish ( Arslan & Barışcı, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The spectrograms obtained at this stage served as inputs for the proposed deep learning models, which predicted the character sequences present in the audio data. A high WER in the prediction scores obtained from deep learning models is a common issue, particularly for agglutinative languages like Turkish ( Arslan & Barışcı, 2020 ). Although CER is lower than WER, significant improvements in WER can be achieved by using a good language model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation